A rosemary extract enriched in carnosic acid improves circulating adipocytokines and modulates key metabolic sensors in lean Zucker rats: Critical and contrasting differences in the obese genotype. Issue 5 (23rd December 2013) - Romo‐Vaquero, María; Larrosa, Mar; Yáñez‐Gascón, María J.; Issaly, Nicolas; Flanagan, John; Roller, Marc; Tomás‐Barberán, Francisco A.; Espín, Juan C.; García‐Conesa, María‐Teresa
<x xml:space="preserve">Abstract</x> Scope Carnosic acid (CA) and rosemary extracts (REs) have antiobesity effects but the mechanisms are not understood. We investigated some of the potential mechanisms contributing to the metabolic effects of an RE enriched in CA. Methods and results An RE (∼40% CA) was administered to lean (Le, fa/+) and obese (Ob, fa/fa) female Zucker rats for 64 days. Several adipocytokines, brain‐derived neurotrophic factor, phosphorylated AMP‐activated protein kinase, and hepatic gene expression changes were investigated. The RE significantly decreased circulating tumor necrosis factor alpha (RE/CT = 0.36, p < 0.0003), IL‐1β (0.48, p < 0.032), and leptin (0.48, p < 0.002), and upregulated adiponectin (1.47, p < 0.045) in the Le rats. The RE also induced phase I and phase II gene expression and the peroxisome proliferator‐activated receptor gamma coactivator 1‐alpha. Notably, the RE decreased adipose phosphorylated AMP‐activated protein kinase and did not affect hepatic peroxisome proliferator‐activated receptor gamma coactivator 1‐alpha in the Ob rats. Conclusion Our results show that an RE rich in CA exerts anti‐inflammatory effects and affects hepatic metabolism in normal Le rats. We report significant differences in the expression and regulation of key metabolic sensors between Le and Ob rats that may contribute to explain the different ability of the two genotypes to respond to the RE.